Evaluation of host plant resistance to Alfalfa mosaic virus in peppers in greenhouse and field - Amiri-Kazaz, Lara M.; Nachappa, Punya; Szczepaniec, Adrianna (Frontiers in Agronomy, 2025)
Alfalfa mosaic virus (Bromoviridae: Alfamovirus) (AMV) is an emerging pathogen of peppers (Capsicum spp. L.) in Colorado that has caused significant yield losses. The virus is transmitted non-persistently by aphids, and few management options are available to suppress the virus. Thus, the goal of this work was to evaluate the effectiveness of host plant resistance against AMV. We evaluated 20 commercially available pepper cultivars for resistance to AMV in the greenhouse and validated resistance in a subset of these under field conditions on commercial farms in Pueblo, CO. Virus infection was assessed by quantifying symptom severity and measuring incidence of AMV symptoms and disease incidence through ELISAs. We found in the greenhouse that 20% of cultivars were asymptomatic to AMV despite being infected. Additionally, 10% of cultivars displayed symptoms but never tested positive for the virus. Field trials on commercial farms revealed that half of the tested cultivars (‘Bayonet’, ‘Masivo’, ‘Mosco’, and ‘Revolution’) maintained low symptom severity and infection incidence throughout the season. Cultivar responses were consistent between greenhouse and field settings, and temporal changes in susceptibility were also observed in two cultivars (‘Masivo’ and ‘Lumbre’). Our findings identify several pepper cultivars with resistance to AMV that could be integrated into pest management programs. These results also provide a foundation for future research aimed at breeding AMV-resistant peppers and developing comprehensive management strategies for this emerging viral disease.